Self-Consciousness: a novel story - Clarke, James (Department of English Language and Literature, 2021)
This document is the result of work probably better suited to a psychologist than a literary scholar, so I make my apologies in advance if what follows seems at times inappropriately confessional, but I'm afraid that my interest in the subject is less academic than it is personal. Though it was never included as part of his academic work, the attached typescript for a graphic novel, Kariba, is the work of James C—, for a time one of my most promising students. Under my supervision for the MA within the Department of Language and Communication, he was engaged in writing a novel (the traditional kind, sans illustrations) of which, tragically, only fragments remain. James took his own life in late 2019 after a long struggle with depression. As his supervisor, I saw first-hand the progress of this terrible disease. Despite the encouragement I gave, James suffered from a lack of self-belief that many will recognise as symptomatic of our age—in which the good lack all conviction, while the worst are full of passionate intensity.